The "bomb" risk elicitation task - Paolo Crosetto; Antonio Filippin (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper presents the Bomb Risk Elicitation Task (BRET), an intuitive procedure aimed at measuring risk attitudes. Subjects decide how many boxes to collect out of 100, one of which containing a bomb. Earnings increase linearly with the number of boxes accumulated but are zero if the bomb is also collected. The BRET requires minimal numeracy skills, avoids truncation of the data, allows to precisely estimate both risk aversion and risk seeking, and is not affected by the degree of loss aversion or by violations of the Reduction Axiom. We validate the BRET and test its robustness in a large-scale experiment, although the task can be performed in the field as well. Choices react significantly to the stakes and to the size of the choice set. Our experiment rationalizes the gender gap that often characterizes choices under uncertainty by means of a higher loss rather than risk aversion.
Keywords: C81; C91; D81; 330; Risk Aversion; Loss Aversion; Elicitation Method